KUALITAS PELAYANAN IZIN MENDIRIKAN BANGUNAN (IMB) PADA KANTOR KELURAHAN SIDODADI KECAMATAN WONOMULYO KABUPATENPOLEWALI MANDAR - Permana, Erwin Ade (Indonesian Journal Of Law Studies, 2023)
This study aims to identify and describe the quality of public services at the Sidodadi Village Office, Wonomulyo District, Polewali Mandar Regency, especially in terms of building permits (IMB) and to know and describe the factors that influence public services at the Sidodadi Village Office, Wonomulyo District, Polewali Mandar Regency, especially in terms of obtaining a building permit (IMB). The research method used is a qualitative method with a descriptive type of research aimed at exploring facts about the quality of public services in the Sidodadi Village. The informants for this study consisted of village heads, secretaries and village staff and the community, so that the total number of informants in this study were 13 people. The results of this study are: The quality of public services in the Sidodadi Village is fairly good. This is in accordance with the results of interviews on the five aspects of service quality, namely: Tangible, Reliability, Responsiveness, Assurance, and Empathy, which obtained satisfactory results, except for facilities in the form of a narrow parking lot. and a slightly hot waiting area. While the factors that influence service performance consist of capabilities and infrastructure factors.